PENERAPAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS TERHADAP PEREDARAN MEREK MOKE DI KOTA KUPANG - Salle Wena, Yohanes De La; Aloysius, Sukardan; Hedewata, Agustinus (Petitum Law Journal, 2023)
Brand is a sign to identify the origin of goods and services (an indication of origin) of a company with the goods and / or services of other companies. Moke is a typical drink from the island of Flores made from siwalan (palm tree) and enau plants. This drink has many names such as sopi, dewe, and moke. But the most familiar and characteristic name of Flores Island is moke. This research is an empirical juridical research, located in Kupang City, The aspects studied in this study are: a) Factors that cause low registration of traditional Moke beverage brands in Kupang City b) Procedures for registering trademark rights of traditional Moke Moke drinks in Kupang City. Data Types and Sources consist of primary and secondary data with data collection techniques, namely by means of interviews and questionnaires, then the data is obtained and analyzed in a qualitative descriptive manner. The main problems in this study are a) What are the factors that cause the low registration of traditional Moke beverage brands in Kupang City? b) What is the procedure for registering trademark rights for traditional moke Moke drinks in Kupang City? The purpose of this study is to determine the factors that cause the low registration of traditional Moke beverage brands in Kupang City and the procedure for registering Moke Moke traditional beverage trademark rights in Kupang City. The results showed that the factors causing the low registration of moke marks in Kupang city were due to the lack of public knowledge about trademark registration, the assumption factor that the mark does not need to be registered, the readiness factor of the community to register its mark, the class determination factor, the expensive factor of trademark registration fees and the assumption that the moke brand liquor is still small and the trademark registration procedure in Kupang city has been regulated in Law No. 20 years 2016 in article 4 of the Trademark Registration Facility Procedure. The trademark registration procedure is very easy and not difficult. Moke brand registration requirements are the first required applicant's personal data, namely name, address, email, cellphone number and the second is needed brand logo or commonly called brand etiquette. After the data is collected, the billing code is printed and paid to the bank, after paying at the bank, it is immediately processed in the application. The advice in this study is that it is expected for producers who own traditional liquor brands to be able to register trademarks with IPR in order to obtain legal protection, so that others cannot misuse existing brands. And it is also expected that the government, especially in this case IPR which handles trademark registration, can socialize the importance of trademark registration, both for these individuals and for others.